Implementing Curriculumn of Madrasah Tsanawiyah in Increasing the Quality of Pesantren Al-Kautsar Al-Akbar Medan - Syafaruddin Syafaruddin; Mesiono Mesiono (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
The implementation of the Tsanawiyah Islamic Boarding School Curriculum in improving quality at the Al-Kautsar Al-Akbar Islamic Boarding School in Medan aims to find out the structure of the Islamic boarding school curriculum and its implementation in the madrasa. This study uses a qualitative approach with a descriptive method, which is to explore data related to the implementation of the pesantren curriculum in the learning process at Madrasah Tsanawiyah and describe the data according to the focus of the study to clarify the purpose of the research. The problem discussed in this paper is how the pesantren curriculum and its implementation in Madrasah Tsanawiyah Al-Kautsar Al-Akbar Medan Islamic School. The results found that structurally the Madrasah Tsanawiyah Al-Kautsar Al-Akbar Medan implemented two curricula, the pesantren education curriculum and the ministry of religion curriculum. The pesantren education curriculum is divided into two curricula. The first is not related to Arabic grammar such as the Qur'an, Hadith, and Morals, this is called the pesantren curriculum. Whereas subjects such as nahwu and sharaf are included in the Arabic curriculum. In implementing the pesantren education curriculum it is not much different from the curriculum of the Ministry of religion. Those who teach the pesantren education curriculum are competent teachers who have special qualifications in the field of religion and all the teachers are pesantren alumni. The method used in learning boarding school education material is to use bandongan and sorogan methods which are carried out classically. The evaluation method used is evaluation with written and practical examinations